Combatants and civilians? Individuals as constructed in international humanitarian law, c. 1864-2020 - Landefeld, Sarina (2021)
This thesis provides a historical account of the changing conceptualisation of individuals in international humanitarian law since 1864. Drawing on social constructivism, a theoretical approach in the discipline of International Relations, it traces how changing understandings of individuals have informed the regulation of participation in hostilities and protection of victims of armed conflicts under the law over time. It highlights how certain ideas, assumptions and biases have been embedded in the legal rules and regulations throughout different periods, and how they influence the law as it exists today. In particular, it examines the role of different actors and discourses in various attempts of creating and shaping international humanitarian law. It reveals the complexity and struggle of constructing the meaning of individuals for the purpose of international humanitarian law, which is often hidden by a conventional narrative of timeless principles or linear progress. Individuals today are believed to be either combatants or civilians under international humanitarian law. This thesis, however, argues that the concepts of combatants and civilians have not evolved in unison, but have been informed by different actors, factors, and dynamics, and developed often independently at distinct times. Overall, the project challenges the conventional understanding that the principle of distinction, i.e. the distinction between combatants and civilians, has been foundational for the rights, obligations and protections of individuals under international humanitarian law since the second half of the nineteenth century.